Interfaces between hexagonal and cubic oxides and their structure alternatives. Issue 1 (December 2017) - Zhou, Hua; Wu, Lijun; Wang, Hui-Qiong; Zheng, Jin-Cheng; Zhang, Lihua; Kisslinger, Kim; Li, Yaping; Wang, Zhiqiang; Cheng, Hao; Ke, Shanming; Li, Yu; Kang, Junyong; et al.
Abstract Multi-layer structure of functional materials often involves the integration of different crystalline phases. The film growth orientation thus frequently exhibits a transformation, owing to multiple possibilities caused by incompatible in-plane structural symmetry. Nevertheless, the detailed mechanism of the transformation has not yet been fully explored. Here we thoroughly probe the heteroepitaxially grown hexagonal zinc oxide (ZnO) films on cubic (001)-magnesium oxide (MgO) substrates using advanced scanning transition electron microscopy, X-ray diffraction and first principles calculations, revealing two distinct interface models of (001) ZnO/(001) MgO and (100) ZnO/(001) MgO. We have found that the structure alternatives are controlled thermodynamically by the nucleation, while kinetically by the enhanced Zn adsorption and O diffusion upon the phase transformation. This work not only provides a guideline for the interface fabrication with distinct crystalline phases but also shows how polar and non-polar hexagonal ZnO films might be manipulated on the same cubic substrate. The control over the crystallographic orientation at functional oxide interfaces is crucial to the performance of oxide-based electronics. Here, Zhou et al. provide a detailed insight into the thermodynamic and kinetic process of nucleation-mediated crystal growth at the ZnO and MgO interface.